Molecular Characterization of Organic Aerosol in Summer Suburban Shanghai Under High Humidity - Xiancheng Tang; Junfang Mao; Dongmei Cai; Zhiwei Zhang; Haixin Nong; Ling Li; Jianmin Chen (Atmosphere, 2025)
In this study, the chemical compositions of PM2.5 (particulate matter < 2.5 μm) and the molecular compositions of methanol-soluble organic carbon (MSOC) in suburban Shanghai during summer were measured to investigate the molecular characteristics of organic aerosol (OA) under high humidity. Diurnal variation analysis reveals the influence of relative humidity (RH) on secondary organic aerosol (SOA) components. Organosulfates (OSs), particularly nitrooxy-OSs, exhibit a positive correlation with increasing humidity rather than atmospheric oxidants in this high-humidity site. This suggests that high RH can promote the formation of OSs, possibly through enhancing particle surface area and volume, and creating a favorable environment for aqueous-phase or heterogeneous reactions in the particle phase. A considerable proportion of CHOS compounds may be derived from anthropogenic aliphatic hydrocarbon derivatives. These compounds exhibit slightly elevated daytime concentrations due to increased emissions of long-chain aliphatics from sources such as diesel combustion, as well as photochemically enhanced oxidation to OSs. In contrast, CHONS compounds increased at night, driven by high-humidity liquid-phase oxidation. Terpenoid derivatives accounted for 13.4% of MSOC and contributed over 40% to nighttime CHONS. These findings highlight humidity’s important role in driving daytime and nighttime processing of anthropogenic and biogenic precursors to form SOA, even under low SO2 and NOx conditions.